TINJAUAN MENGENAI PROSES PENYELESAIAN TERHADAP PENETAPAN SENGKETA HASIL PEMILIHAN SERENTAK BAKAL CALON KEPALA DESA YANG DIANGGAP MELAKUKAN PERBUATAN MELAWAN HUKUM(Studi Putusan Nomor: 12/Pdt.G/2023/PN Kbu) - Refi Shely Ristianti; Lintje Anna Marpaung (JOURNAL OF LAW AND NATION, 2024)
An unlawful act is an act that violates statutory regulations, an act that conflicts with the rights of another person, an act that causes harm to another party, and of course the party who commits the act must compensate the party who has suffered the loss. Article 26 of Law Number 6 of 2014 concerning Villages explains that the duties of the village head are to organize village government, carry out village development, empower village communities, and develop the lives of village communities. The formulation of the problem in this research is what forms of unlawful acts were committed by the defendant in the process of simultaneously selecting village head candidates and how the judge considered them in resolving disputes over the election results. The research method uses a normative juridical approach, namely research carried out by reviewing applicable legislation and an empirical approach carried out by looking at the reality in the field, in the form of interviews to be applied in order to answer problems related to the research problem. The results of this research show that the form of unlawful action that occurred in Decision Number 12/Pdt.G/2023/PN Kbu was because there was a mistake made by the defendant to the plaintiff, namely by providing additional selection of village head candidates outside the provisions relating to procedures for selecting heads. villages that have been regulated in the North Lampung Regent's Regulations. Then the judge's consideration in deciding the case in Decision Number 12/Pdt.G/2023/PN Kbu was that the lawsuit made by the plaintiff did not meet the formal requirements and the judge decided that the lawsuit could not be accepted. This is based on the exception submitted by the defendant, namely explaining that the district court has no authority or absolute competence, the plaintiff's claim is error in persona, the plaintiff's claim is vague (Obscuur Libel) and the petitum of the plaintiff's claim is unclear.